Perancangan Sistem Informasi Kesekretariatan dengan Fitur Notifikasi Real-Time Berbasis Web Framework Laravel (Studi Kasus: Institut Tarumanagara) - Adelya Selsilia Setyadi; Hari Santoso; Sobiyanto Sobiyanto; Sugesti Sugesti (Universitas Batanghari Jambi, 2026)
This study aims to design a Secretariat Information System with real-time notification features using the Laravel web framework at Tarumanagara University. The research methodology includes primary data collection through interviews and secondary data through literature studies. Data analysis was carried out using a qualitative descriptive approach to identify system requirements based on field findings. The system design utilized the Unified Modeling Language (UML) to represent workflows and system functionalities through various diagrams. The coding process implemented Laravel and MySQL due to their flexibility and compatibility with multiple operating systems and programming languages. System testing was performed using the black box testing method to ensure all functional requirements were met. The results show that the system successfully provides a centralized platform for managing incoming letters, outgoing letters, and dispositions digitally. The real-time notification feature effectively delivers automatic alerts to users, improving responsiveness and reducing delays. Furthermore, the system enables comprehensive tracking of letter statuses, making administrative processes more transparent, efficient, and well-documented.